The teaching internship as a locus for the process of (trans)formation and (re)construction of teaching knowledge - Sousa, Alba Patricia Passos de; Bragança, Inês Ferreira de Souza (Debates em Educação, 2026)
The authors present a reflection on the experiences and learning gained during the Teaching Internship Program (PED) offered by the Graduate Program in Education at the State University of Campinas (UNICAMP). This program was part of the supervised internship course in the first semester of 2020, and took place in Campinas, São Paulo, Brazil. The text problematizes the process of developing the competencies and skills inherent to teaching activity, in order to understand how these skills are integrated into undergraduate and postgraduate programs for the effective development of teaching/learning. I realised the importance of emotional relationships and of listening attentively to the realities that prevent us from being well at various times in our lives.